(untitled) (Journal of Management and Business Education, 2022)
The global pandemic caused by COVID-19 has affected higher education due to the reduction in attendance in classrooms. As a consequence, teaching methodologies have been adapted to hybrid classes where the virtual space has become the new communication place between teachers and students. From this perspective, virtual teaching has become an opportunity for teaching innovation in times of COVID-19. This article is a case study on teaching innovation applied to a degree subject through the Transformative Learning methodology, whose objective is to strengthen students’ teamwork skills through a Service-Learning project with disabled children. Once the project was finished, the students expressed their level of satisfaction with this project, reinforcing these skills through a project in the community.